2010
DOI: 10.1089/neu.2010.1325
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Improves Hemodynamics and Reduces Oxidative Stress in the Brains of Newborn Piglets with Hypoxia-Reoxygenation Injury

Abstract: Reactive oxygen species have been implicated in the pathogenesis of hypoxic-ischemic injury. It has been shown previously that treating an animal with N-acetyl-L-cysteine (NAC), a scavenger of free radicals, significantly minimizes hypoxic-ischemic-induced brain injury in various acute models. Using a subacute swine model of neonatal hypoxia-reoxygenation (H-R), we evaluated the long-term beneficial effect of NAC against oxidative stress-induced brain injury. Newborn piglets were randomly assigned to a sham-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Cheung et al have examined the effects of antioxidant treatment in this model of resuscitation. Treatment with NAC, which blocks the production of superoxide and peroxynitrite, results in decreased oxidative stress, improved hemodynamics and tissue perfusion, and decreased platelet aggregation after hypoxia-reoxygenation [55], [56], [57], [58], [59], [60]. However, the mechanisms by which oxidative and nitrative stresses promote inflammation have not been fully defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheung et al have examined the effects of antioxidant treatment in this model of resuscitation. Treatment with NAC, which blocks the production of superoxide and peroxynitrite, results in decreased oxidative stress, improved hemodynamics and tissue perfusion, and decreased platelet aggregation after hypoxia-reoxygenation [55], [56], [57], [58], [59], [60]. However, the mechanisms by which oxidative and nitrative stresses promote inflammation have not been fully defined.…”
Section: Discussionmentioning
confidence: 99%
“…In separate experiments, as described previously [59], [60], an additional group of animals exposed to 30 minutes of 100% O 2 resuscitation were treated with a bolus of 150 mg/kg N-acetylcysteine (NAC) starting at the onset of 100% O 2 resuscitation followed by a 20 mg/kg/h infusion for the duration of the experiment. Samples were obtained from five groups: Control animals were euthanized after undergoing surgical preparation and anesthesia but prior to asphyxia; the post asphyxia group was harvested at the end of asphyxia prior to any resuscitation; and three groups of animals were harvested at 150 minutes after the 30 minute exposure to either 21% O 2 resuscitation, 100% O 2 resuscitation, or 100% O 2 resuscitation with NAC treatment.…”
Section: Methodsmentioning
confidence: 99%
“…With hypothermia now recognized as the clinical standard of care, the addition of other neuroprotective agents to hypothermia treatment are being investigated to improve outcomes further (Barks et al, 2010, Liu et al, 2012, Hobbs et al, 2008, Fan et al, 2013). N-acetylcysteine (NAC) is a promising antioxidant therapy that impacts many pathways of injury and has established neuroprotective effects in animal models of HI and neuroinflammation (Jatana et al, 2006, Paintlia et al, 2004, Liu et al, 2010). Immune and inflammatory responses to HI are modulated by cellular redox status, and increased apoptotic signaling pathways are present in cells with low anti-oxidant reserves (Lu, 2009, Cook et al, 2004, Circu and Aw, 2010, Wang and Kaufman, 2012, Ten and Starkov, 2012, Jager et al, 2012).…”
Section: Introduction1mentioning
confidence: 99%
“…Several studies have demonstrated that N-acetylcysteine (NAC), a precursor of the endogenous antioxidant glutathione, has potential organ- and neuroprotective abilities when administered immediately after neonatal hypoxia-reoxygenation [5,6,7]. Recently, it has been revealed that NAC amide (NACA), an NAC derivate with higher bioavailability and enhanced antioxidant properties [8,9], may significantly mitigate the detrimental consequences of various toxic substances in different organs, including the lungs and kidneys [10,11,12].…”
Section: Introductionmentioning
confidence: 99%